2020
DOI: 10.3389/fcell.2020.600867
|View full text |Cite
|
Sign up to set email alerts
|

Roles of MicroRNAs in Bone Destruction of Rheumatoid Arthritis

Abstract: As an important pathological result of rheumatoid arthritis (RA), bone destruction will lead to joint injury and dysfunction. The imbalance of bone metabolism caused by increased osteoclast activities and decreased osteoblast activities is the main cause of bone destruction in RA. MicroRNAs (MiRNAs) play an important role in regulating bone metabolic network. Recent studies have shown that miRNAs play indispensable roles in the occurrence and development of bone-related diseases including RA. In this paper, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 100 publications
1
8
0
Order By: Relevance
“…RA pathogenesis is complex but the main pathologic features are synoviocyte proliferation and destruction of cartilage and bone. Collectively, these processes can cause a significant amount of pain and affect the quality of life adversely [ 12 ]. Joint symptoms can be divided into two types: synovial inflammation and destruction of joint structure.…”
Section: Discussionmentioning
confidence: 99%
“…RA pathogenesis is complex but the main pathologic features are synoviocyte proliferation and destruction of cartilage and bone. Collectively, these processes can cause a significant amount of pain and affect the quality of life adversely [ 12 ]. Joint symptoms can be divided into two types: synovial inflammation and destruction of joint structure.…”
Section: Discussionmentioning
confidence: 99%
“…showed that genes in the lncRNA-mRNA interaction network were enriched for terms related to production and function of miRNAs, which play important role in bone destruction of rheumatoid arthritis (Zhao et al, 2020), indicating that DE lncRNAs may also function by regulating miRNAs to influence the expression of targeted mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous reports indicating FoxO1 in SPAHO syndrome ( Berthelot et al, 2018 ), another nine genes including FoxO3 in the FoxO signaling pathway was also found to be regulated by DE lncRNAs in the SAPHO group. GO analysis showed that genes in the lncRNA-mRNA interaction network were enriched for terms related to production and function of miRNAs, which play important role in bone destruction of rheumatoid arthritis ( Zhao et al, 2020 ), indicating that DE lncRNAs may also function by regulating miRNAs to influence the expression of targeted mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of RA is complex; the main pathological features are synovial cell proliferation and the destruction of cartilage and bone. Collectively, these processes can cause a significant amount of pain and can adversely affect the quality of life [12]. Joint symptoms can be divided into two types: synovial inflammation and joint structure destruction.…”
Section: Discussionmentioning
confidence: 99%